Stigmatizing attitudes of tertiary hospital physicians towards people with mental disorders in Saudi Arabia - Saad, Sami Y. (Saudi Med J, 2019)
OBJECTIVES: To measure stigma among doctors in one of the major specialized hospitals in Saudi Arabia. METHODS: This cross-sectional study was conducted at King Abdullah Medical City, Jeddah, Saudi Arabia between October and November 2018. Eighty physicians were recruited in this study. The participants administered the sociodemographic questionnaire as well as the Mental Illness Clinicians’ Attitude 4th version (MICA 4). RESULTS: The overall MICA score ranged between 31 and 61 with a mean±SD of 45.75±7.54. The highest reported score was among outpatient physicians (51.33±6.66), while the lowest score was among consultants/assistant consultants (43.17±7.82). CONCLUSION: The results of this study showed a relatively high MICA-4 score that could indicate a high stigmatizing attitude among physicians toward patients with mental illnesses compared with the other MICA-4 studies. Thus, training workshops could improve the attitudes in the short-term.